Community Rights Facing Criminal Law in a Human Rights Perspective - Harisman Harisman (RIRAI Publisher, 2020)
Legal protection is one form of human rights that must be obtained by everyone, especially with regard to the application of criminal law that can have the impact of violations and restrictions on the freedom of others as a form of human rights. It is not uncommon for people's rights to be questioned or even contested when dealing with criminal law. To answer this problem, a study was conducted using the legal research method through a normative jurudical approach which was intended to collect secondary data obtained from the literature in the form of primary legal materials, secondary legal materials and tertiary legal materials. The materials collected were analyzed qualitatively descriptive. Based on the analysis conducted, it is clearly seen that people's rights in criminal law are part of human rights that must get respect and protection in order to maintain human dignity through efforts that include: equality before the law, presumption of innocent, non-retroactive and legal assistance, and not tortured, punishment or cruel, inhumane treatment, degrading human dignity and dignity, and not treated arbitrarily.